Dancing into the Divine: The Hymn of the Dance in the Acts of John - Bowe, Barbara Ellen (Journal of early Christian studies, 1999)
This study examines the "Hymn of the Dance" from the Acts of John in order to explicate its literary and rhetorical character and to discern its theological function for this community of Johannine Gnostic Christians of the late 2nd or early 3rd centuries. As a performative text, the hymn both celebrates and enacts the mystery it proclaims, namely, the unity between the Lord as revealer, the One revealed "on high" and the faithful recipients of the revelation who learn this mystery through the rhythm of this hymnic dance. Moreover, when viewed as representative of at least one "gnostic wing" of Johannine Christianity, this hymn provides witness to the heterodox tradition of Johannine theology and practice and gives us a glimpse of the "intra-Johannine polemic" at work in early Christianity.